PENINGKATKAN SIKAP KEMANDIRIAN DAN PRESTASI BELAJAR IPAS MELALUI MODEL PROBLEM BASED LEARNING (PBL) DENGAN MENGGUNAKAN MEDIA SCRAPBOOK - Afifah, Fadhila Marsya; Muslim, Arifin (JURNAL PENDIDIKAN DASAR PERKHASA: Jurnal Penelitian Pendidikan Dasar, 2025)
This study aims to improve independence attitudes and Science (IPAS) learning achievement of fifth-grade students at SDN 3 Purbalingga Lor through Problem-Based Learning (PBL) using scrapbook media. The research employed Classroom Action Research (CAR) conducted in two cycles, each consisting of two meetings. The subjects were 25 students, comprising 12 boys and 13 girls. Data were collected using both test and non-test techniques, including observation sheets, questionnaires, and documentation. Data analysis was carried out using quantitative and qualitative descriptive methods. The results indicated improvements in both independence attitudes and learning achievement. The independence attitude score increased from 2.49 in cycle I (poor category) to 3.29 in cycle II (very good category). Meanwhile, learning achievement increased from 50% mastery in cycle I (fair category) to 88% in cycle II (very good category). This study confirms that the implementation of PBL assisted by scrapbook media effectively enhances students’ independence and Science learning outcomes.